PENGELOLAAN ARSIP PADA BADAN PERPUSTAKAAN DAN KEARSIPAN DAERAH PROVINSI JAWA BARAT - Anbarrini, Ririn (2016)
Penelitian ini menjawab permasalahan penelitian, ialah "Bagaimana proses pengelolaan arsip yang dilakukan di Bapusipda Jabar?." Secara khusus rumusan masalah ini terdiri dari: (1) Bagaimana kesesuaian program pengelolaan arsip Bapusipda Jabar dilihat dari aspek Context?; (2) Bagaimana kondisi faktor penunjang program pengelolaan arsip Bapusipda Jabar dilihat dari aspek Input?; (3) Bagaimana pelaksanaan program pengelolaan arsip Bapusipda Jabar dilihat dari aspek Process?; (4) Bagaimana keberhasilan program pengelolaan arsip Bapusipda Jabar dilihat dari aspek Product?. Penelitian ini bertujuan mengevaluasi proses pengelolaan arsip pada Bapusipda Jabar dan sesuai atau tidak dengan standar yang telah ditetapkan yaitu UU No. 43 tahun 2009 tentang Kearsipan dan Peraturan Gubernur No. 40 tahun 2008 tentang Tata Kearsipan. Penelitian dilakukan di Badan Perpustakaan dan Kearsipan Jawa Barat terletak di Jl. Kawaluyaan Indah II No. 4 Bandung. Metode penelitian yang digunakan adalah statistik deskriptif, menggunakan model evaluasi CIPP. Teknik analisis data menggunakan Kai Kuadrat. Populasi dan sampel penelitian ini adalah seluruh staf bagian pengelolaan arsip Bapusipda Jabar. Secara umum, hasil penelitian menunjukkan proses pengelolaan arsip yang dilaksanakan di Bapusipda Jabar berjalan baik dan sesuai dengan standar. Simpulan khusus, hasil penelitian menunjukkan bahwa proses pengelolaan arsip dilihat dari aspek context, input, process dan product dinilai sesuai dengan standar yang ada. ;---This research answered the research question, there is "How is the process of archive management implemented in West Java Regional Institution of Library and Archival?. Specifically, the formulations of research questions in this research included: (1) How is the suitability of archive management program in West Java Regional Institution of Library and Archival analyzed from the aspect of Context?; (2) How is the condition of supporting factor of archive management program in West Java Regional Institution of Library and Archival analyzed from the aspect of Input?; (3) How is the implementation of archive management program in West Java Regional Institution of Library and Archival analyzed from the aspect of Process?; (4) How is the success of archive management program in West Java Regional Institution of Library and Archival analyzed from the aspect of Product?. This research is an evaluative study which was aimed to evaluate whether the process of archive management implemented in West Java Regional Institution of Library and Archival has been suitable or not to the assigned standard in the Constitution No 43 Year 2009 about the Archival and Governor Rule No 40 Year 2008 about Archival Management of West Java Provincial Government. This research was conducted in West Java Regional Institution of Library and Archival which is located in Kawaluyaan Indah Street No.4 Bandung. This research used quantitative approach, where the research method applied was descriptive statistics with CIPP evaluation model. The technique of data analysis which had been used in this research was Chi Square. Population and sample in this research included archive administrators or archivists in West Java Regional Institution of Library and Archival. Generally, the results of the research show that the process of archive management implemented in West Java Regional Institution of Library and Archival has been running well and suitable to the assigned standard. Specifically, the results show that process of archive management analyzed from the aspect of context, input, process, and product is well run and suitable to the assigned standard.